STUDY OF CHARACTERISTICS PHYSICAL AND CHEMICAL FISHING AREA JARING INSANG (Gill net) AT WATERS RUPAT UTARA BENGKALIS DISTRICT RIAU PROVINCE - ', Kurniawan; ', Usman; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted on September-October 2014 at the waters of the Rupat Utara Bengkalis district Riau Province, using survey method. Data taken consisted of waters environment parameters area of the physical and chemical include the water temperature, salinity, current speed, brightness, depth, and the degree of acidity (PH). Measurements were performed for ten days along with decision gill net. During the 10 days of observation obtained catches up to 94.5 kg, catches the highest number of 16 kg and the lowest catch is 7 kg, with the physical and chemical conditions. 270-300 C temperature, salinity 25-29 ‰, current speed from 0.10 to 0.33 m / sec, the brightness of 0.57 m - 1.22 m, depth of 18-30 m, and the degree of acidity (pH) 6- 8. Multiple linear regression analysis showed a very strong correlation between the catch with the environmental parameters with regression coefficient 0.948 and turns physical and chemical parameters waters have contributed to the variation 89.9% on the results of fishing.Keywords: waters Rupat Utara, gill net, environment parameters, multiple linear regression